Environmental scanning and effectiveness in strategic planning - Che Ishak, Ismila (2004)
Environmental Scanning is defined as the systematic collection and monitoring of information that describes changes in the environment in order to identify and assess emerging developments in political, social and technological trends, and events that may affect the strategic and tactical objectives of an organization. The effectiveness of strategic planning is directly related to the capacity for the environment scanning.